Comparison of the effect of Morphine and Fentanyl in patients with acute coronary syndrome receiving Ticagrelor - The COMET (Comparison Morphine, Fentanyl and Ticagrelor) randomized controlled trial. (1st May 2021) - Senguttuvan, Nagendra Boopathy; Suman, Febe; Paneerselvam, TamilAnbu; Malepati, Balakrishna; Ramesh, Sankaran; Vallivedu, Mano Vikash; Badimela, Phalgun; Ramadoss, Mahalakshmi; Iyer, Meena; Krishnamurthy, Preetam; Vinod Kumar, Balakrishnan; Balasubramaniyan, Jayanthy Venkata; et al.
Abstract: Introduction: Dual antiplatelet therapy (DAPT) remains the cornerstone of acute coronary syndrome (ACS) management, and ticagrelor is one of the commonly used second antiplatelet agents. There is some evidence to suggest that morphine may reduce the antiplatelet effect of ticagrelor. Methods and results: In a single-center, randomized controlled trial, we compared the effect of morphine and fentanyl on platelet aggregation (PA) among patients with ACS treated with ticagrelor. Platelet aggregation was studied by automated light transmittance aggregometry (LTA) at baseline, and at 2 h after ticagrelor loading. The primary outcome was the difference in the maximal inhibition of platelet aggregation [IPA(%)] between the groups at 2 h. Pain relief, and drug-related adverse events were secondary outcomes. Of 136 patients randomized, 70 received fentanyl and 66 received morphine. At baseline, the median (IQR) platelet aggregation [61.35% (54.6 to 70) Vs. 58.8% (52.7 to 72.9)] were comparable between the groups. There was no statistically significant difference between the fentanyl and the morphine groups in IPA at 2-h [85.88%(64.65–98.16) and 81.93%(44.2–98.03), p  = 0.09]. However, morphine use was independently associated with a PA of >30% at 2 h ( p  < 0.009). There was no difference in adverse events. Conclusion: In patients with ACS, there was no significant difference between the use of fentanyl or morphine on the effect of ticagrelor on PA. (CTRI/2018/04/013423). Highlights: Morphine is the most commonly used analgesic in patients with acute coronary syndrome(ACS). There is some evidence to suggest that morphine may reduce the antiplatelet effect of ticagrelor. This is the first RCT to compare the effect of morphine and fentanyl on the platelet inhibitory effect of ticagrelor in patients with acute coronary syndrome using LTA. We found that the effect of morphine on the antiplatelet effect of ticagrelor is not different from that of fentanyl in patients with ACS.Nevertheless, we found that the use of morphine was independently associated with a residual PA of >30% at two hours. We can use morphine or fentanyl as analgesic and anti-anxiety agents in patients with ACS pending a large multicentric- randomized study powered for hard-end points which investigates these drugs along with another active control like acetaminophen or placebo in the presence and absence of pro-kinetic agents like metoclopramide using a factorial design RCT that can answer our question.